Politics of Tolerance: Ethics of the Republic, Populism, and Totalitarianism in the 2024 Contest - Fajar (Jurnal Ushuluddin: Media Dialog Pemikiran Islam, 2024)
This article reviews Political Tolerance; The Ethics of the Republic, Populism, and Totalitarianism in the Context of the 2024 Contestation. The study aims to illustrate the factors influencing changes in an individual's political tolerance during the 2024 presidential election contest. This research employs a qualitative method utilizing instruments such as literature studies, observation, analysis of conference outcomes, and data collection from informants through interviews, with the researcher acting as the key instrument. The data sources for this study are interviews conducted with lecturers from various programs in the Faculty of Ushuluddin and Philosophy at UIN Alauddin Makassar. The findings of this research highlight the extent of academic discussions and informants’ perspectives on political tolerance, the ethics of the republic, and populism, as viewed by scholars from various scientific backgrounds such as politics, sociology, religious studies, Qur'anic studies, and hadith interpretation. These perspectives are analyzed based on both factual and imaginative understandings of the ethics of the republic and the human condition. The researcher seeks to explore how deeply intellectualism and academic expertise within the university context perceive issues related to the human condition and the ethics of the republic.